Postwar Japan : growth, security, and uncertainty since 1945 - Green, Michael J.; Cooper, Zack (Researcher in security studies) (Center for Strategic & International Studies, 2017)
Japanese security, economic, institutional, and development policies have undergone a remarkable evolution in the 70 years since the end of World War II. Distinguished Japanese scholars reflect on the evolution of these policies and draw lessons for coming decades, spotlighting emerging Japanese thinking on key issues facing the U.S.-Japan alliance.